2001
DOI: 10.4049/jimmunol.166.12.7462
|View full text |Cite
|
Sign up to set email alerts
|

A Filarial Nematode-Secreted Phosphorylcholine-Containing Glycoprotein Uncouples the B Cell Antigen Receptor from Extracellular Signal-Regulated Kinase-Mitogen-Activated Protein Kinase by Promoting the Surface Ig-Mediated Recruitment of Src Homology 2 Domain-Containing Tyrosine Phosphatase-1 and Pac-1 Mitogen-Activated Kinase-Phosphatase

Abstract: Unraveling the molecular mechanisms by which filarial nematodes, major human pathogens in the tropics, evade the host immune system remains an elusive goal. We have previously shown that excretory-secretory product-62 (ES-62), a homologue of phosphorylcholine-containing molecules that are secreted by human parasites and which is active in rodent models of filarial infection, is able to polyclonally activate certain protein tyrosine kinase and mitogen-activating protein kinase signal transduction elements in B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 39 publications
2
33
0
Order By: Relevance
“…11 and results not shown). Use of this mechanism to regulate B cell proliferation is consistent with our previous findings that immunomodulatory products secreted by filarial nematodes can elicit B cell unresponsiveness by priming uncoupling of BCR-Erk-MAP kinase signaling by the MAP kinase phosphatase, Pac-1 (25).…”
Section: Mechanism Of Bcr-mediated Down-regulation Of Cycling Erk-mapsupporting
confidence: 89%
“…11 and results not shown). Use of this mechanism to regulate B cell proliferation is consistent with our previous findings that immunomodulatory products secreted by filarial nematodes can elicit B cell unresponsiveness by priming uncoupling of BCR-Erk-MAP kinase signaling by the MAP kinase phosphatase, Pac-1 (25).…”
Section: Mechanism Of Bcr-mediated Down-regulation Of Cycling Erk-mapsupporting
confidence: 89%
“…5). In our studies, as for other filarial models, no lymphoproliferation could be measured by stimulation with Ad or larval worm extracts (13,20,21,40).…”
Section: Vol 71 2003 Resistance To Murine Filaria Litomosoides Sigmmentioning
confidence: 66%
“…44). We have previously shown that exposure to ES-62 suppresses subsequent Ag-mediated proliferation of B cells by uncoupling the Ag receptors (B cell receptor) from extracellular signal-regulated kinase/mitogen-activated protein kinase-dependent proliferative signaling (45)(46)(47). Such desensitization of B cell clonal expansion can be mimicked by the PC component of ES-62 (48).…”
Section: Figure 6 Es-62 Inhibits Tnf-␣ Production From Human T Cellsmentioning
confidence: 99%